Estudo do desempenho de microrredes ilhadas baseado em análises de segurança estática e dinâmica em sistemas elétricos de potência - Gurski, Erico (2020)
The islanded microgrids operation has been an object of interest to the technical-scientific community, as it brings advantages and also challenges regarding its design. For such a mode of service to be possible, the microgrid must be intentionally planned, aiming at satisfactory performance when facing a defined set of possible operating scenarios. In electrical power systems, static and dynamic security assessment are used to determine the safety of the system when subjected to previously determined disturbances, through power flow and stability studies. This research presents a computational tool is proposed to assist in the islanded microgrids operation planning. This tool includes a set of studies essential to islanded systems’ operation, according to the prescription of the international standard IEEE Std. 1547-4, covering power flow and frequency and transient stability studies. The use of some performance indicators benchmarks the microgrid operation. All these studies are done through a computational routine, developed in MATLAB, for a study horizon of one day of operation, discretized in 24 hours. The load and generation curves are deterministic. The performance indicators are based on existing indices, prescribed by the National Electric Energy Agency (ANEEL) for the distribution system. The microgrid structure under study consists of a portion of a radial distribution system, containing a reduced number of protection and sectioning elements. This research presents a load shedding strategy considering both security analyzes (static and dynamic), aiming to keep the voltage and frequency of the microgrid within the stipulated ranges. Some operational scenarios over a 69 bus test system provide the means to analyze the approach proposed. From the case studies, it is possible to perceive the influence of the choice of the connection bar of the slack generator on the performance of both voltage and frequency. Besides, it is clear that the activation of the load shedding strategy brings benefits to the quality of the product (voltage and frequency). However it affects the quality of the service (continuity in the energy supply). In this way, choosing the best operating topology of the microgrid, whether or not activating the load shedding strategy, depends on the weighting assigned to the indicators.